The German labour market reforms in a European context: A DSGE analysis - Claudia Busl; Atılım Seymen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
While a widespread consensus exists among macroeconomists that the German labour market reforms in 2003-2005 have successfully contributed to the decline of the unemployment rate, critics claim that the reforms led to wage restraint and consequently consumption dampening accompanied by beggar-thy-neighbour effects, harming Germany's trade partners. We check up on the validity of these arguments by means of a two-country DSGE model featuring intra-industry trade and labour market frictions. Our results suggest that the disproportional growth of GDP (labour productivity) in comparison to consumption (wages) are only partially driven by the reforms. However, we do not find that the reforms contribute to Germany's trade surplus and cause negative spillovers to trading partners in terms of output and employment.
urn:nbn:de:bsz:180-madoc-352585
Keywords: E24; E61; E65; F42; J38; J63; 330; labour market reforms; search and matching; spillover; dynamic stochastic general equilibrium models